Pemberdayaan Ekonomi Desa Melalui Badan Usaha Milik Desa (Bumdes) Desa Timbang Jaya Kecamatan Bahorok Kabupaten Langkat - Muhammad Nur Iqbal (Medan Resource Center, 2021)
Badan Usaha Milik Desa (BUMDes) is one of the government programs in an effort to increase economic empowerment in a Village through the management of the potential that exists in a village where the budget on subsidies by the government to create independence village. Managing funds BUMDes itself is fully implemented from the village, for the village and to the village itself. The focus of the activities of the community towards economic empowerment of the village through BUMDes in Desa Timbang Jaya Kecamatan Bahorok, Langkat, community service activities carried out through the activities of the seminar, which aims to provide an understanding of the Village and community in the improvement of the welfare and economy of the Village through BUMDes. Implemntasi the results of community service activities is the outsider cover the Village Government and Village communities Timbang Jaya as well as be able to publish these activities into National Accredited Journal. then, through a program of community service, this can be the implementation of the socialization of the economic empowerment of the village via the Village-Owned Enterprises (BUMDes).